Що ж таке біотична і ландшафтна різноманітності? - Голубець, М.А. (Інститут ботаніки ім. М. Г. Холодного НАН України, 2006)
В зависимости от подходов, методов, средств и прикладных потребностей целесообразно различать три категории биотического разнообразия: общую (интегральную), отраслевую (объектную) и производственную (прикладную). Согласно программным заданиям Конференции ООН в Рио-де-Жанейро, производственное разнообразие включает три его вида: видовое (организменное, индивидуумное), популяционное и экосистемное. Ландшафтное разнообразие разделяется на две категории: ландшафтно-географическое (традиционно-ландшафтное) и пейзажное (гуманистическое), которое отвечает определению "Всеевропейской стратегии сохранения биологического и ландшафтного разнообразия" и гармонизирует с программами охраны редкостных, уникальных и значимых биотопов и экосистем, а также формирования экологической сети. Depending on the approaches, methods, means and applied goals of demands, it is reasonable to distinguish three categories of biotic diversity: general (integral), disciplinary (objective), and productive (applied). According to the program goals of The Rio de Janeiro UN Conference, productive diversity includes three kinds: species (organism, individual), population and ecosystem diversity. Landscape diversity is subdivided into two categories: geographical (traditionally landscape) and scenery (humanistic) diversity, which corresponds to the definition of the Pan-European Strategy for Conservation of Biological and Landscape Diversity and is in harmony with the programs of conservation of the rare, unique and important habitats or ecosystems as well as with the formation of the ecological network.